PETROBRAS AND THE STATE OF RIO DE JANEIRO ON THE ROUTE OF THE GLOBAL ENERGY TRANSITION - Guerra, Wander (Cadernos do Desenvolvimento Fluminense, 2026)
Climate change has taken over the global debate in recent years, and with this, the energy transition has gained relevance on the agenda of companies, governments and institutions. Rio de Janeiro, being the Brazilian state that produces the most oil, finds itself on the path of strategies that directly affect the oil industry, mainly based on the logic of decarbonization and the imperatives of green capitalism. The effects of the energy transition with a view to reducing the burning of fossil fuels can be diverse depending on how slow the transitional process will be. This article, based on a bibliographical review and exploratory research, seeks to present possible impacts of the global energy transition on the economy of Rio de Janeiro, focusing on the activities of Petróleo Brasileira S.A, the largest Brazilian state-owned company that has concentrated actions and investments in the southeast region of Brazil.. We will see that the energy transition led by green capitalism, mainly from so-called renewable energies, can bring negative impacts to Rio de Janeiro society, while it could perpetuate possible environmental sacrifices by the oil industry. At the same time, by preventing a broad consolidated infrastructure of the oil industry, Rio de Janeiro can be at the forefront of a fair energy transition in Brazil and Petrobras has a central role in the process.